2010
DOI: 10.1111/j.1467-7652.2010.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Two EguCBF1 genes overexpressed in Eucalyptus display a different impact on stress tolerance and plant development

Abstract: SummaryTwo C-repeat binding factor genes (EguCBF1a ⁄ b), isolated from E. gunnii and differentially cold-regulated, were constitutively overexpressed in a cold-sensitive Eucalyptus hybrid. In addition to the expected improvement on freezing tolerance, some resulting transgenic lines (EguCBF1a-OE and EguCBF1b-OE) exhibited a decrease in stomata density and an over-accumulation of anthocyanins also observed to a lesser extent in a cold-acclimated control plant. Given that the induction of five putative CBF targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 49 publications
9
50
1
4
Order By: Relevance
“…8B). It has been well documented that DREBs strongly enhance abiotic stress tolerance and cause dwarfism (Liu et al, 1998;Hsieh et al, 2002;Gilmour et al, 2004;Kasuga et al, 2004;Navarro et al, 2011). At present, field-grown OsSIK2-t plants exhibit a severe dwarf phenotype but strong salt tolerance compared with OsSIK2-f plants (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…8B). It has been well documented that DREBs strongly enhance abiotic stress tolerance and cause dwarfism (Liu et al, 1998;Hsieh et al, 2002;Gilmour et al, 2004;Kasuga et al, 2004;Navarro et al, 2011). At present, field-grown OsSIK2-t plants exhibit a severe dwarf phenotype but strong salt tolerance compared with OsSIK2-f plants (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…Shao et al, (2002) developed transgenic E. urophylla events showing an increased resistance by 35% against the bacterial wilt disease caused by the pathogen, Pseudomonas solanacearum. Navarro et al (2010) reported that two cold induced transcription factors that specifically bind to C binding factor genes namely EguCBF1a/b were isolated from E. gunni and constitutively over-expressed in a cold sensitive eucalyptus hybrids. The transgenic trees showed improved freeze tolerance and opened new avenues for freeze tolerant research in eucalyptus.…”
Section: Eucalyptsmentioning
confidence: 99%
“…The ability to successfully grow under different kinds of abiotic stress represents an important trait in eucalypts plantations. Transgenic lines in several eucalypt species with tolerance to salinity, low temperatures and drought were obtained by YamadaWatanabe et al (2003) and Navarro et al (2011).…”
Section: Eucalyptsmentioning
confidence: 99%